2016
DOI: 10.4067/s0718-19572016000300006
|View full text |Cite
|
Sign up to set email alerts
|

Relación del crecimiento, condición y supervivencia del ostión del Pacífico Crassostrea gigas y las variables ambientales, cultivado en suspensión en el sistema lagunar Navachiste-Macapule, Sinaloa, México

Abstract: ARTÍCULORelación del crecimiento, condición y supervivencia del ostión del Pacífico Crassostrea gigas y las variables ambientales, cultivado en suspensión en el sistema lagunar Navachiste-Macapule, Sinaloa, México Abstract.-Evaluation of potential culture sites represents a 'good practice' alternative to support the development of oyster industry at the northeast of Mexico. The relationship of growth, condition and survival of Crassostrea gigas with the environmental parameters was studied at the Navachiste-Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
(25 reference statements)
3
10
0
6
Order By: Relevance
“…Osuna-Martínez et al (2010, 2011 performed metal analysis by sampling cultured oysters seasonally from four coastal lagoons in this region (El Colorado, Santa María La Reforma, Altata and Ceuta), and Bergés-Tiznado et al (2013a, b) reported the levels of arsenic and arsenic species in cultured oyster (C. gigas and C. corteziensis) from coastal lagoons in the same area, but only one work by Páez-Osuna and Osuna-Martínez (2015), who collected wild C. corteziensis and C. palmula specimens, has studied the SINM lagoon system. Among the most important bivalve species cultivated in the north coast of Sinaloa are the oysters C. gigas (Rodríguez-Quiroz et al 2016) and C. corteziensis (Leal-Sepúlveda 2011), the clam Megapitaria squalida (Álvarez-Dagnino 2013), and the pen shell Atrina maura (Góngora-Gómez et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Osuna-Martínez et al (2010, 2011 performed metal analysis by sampling cultured oysters seasonally from four coastal lagoons in this region (El Colorado, Santa María La Reforma, Altata and Ceuta), and Bergés-Tiznado et al (2013a, b) reported the levels of arsenic and arsenic species in cultured oyster (C. gigas and C. corteziensis) from coastal lagoons in the same area, but only one work by Páez-Osuna and Osuna-Martínez (2015), who collected wild C. corteziensis and C. palmula specimens, has studied the SINM lagoon system. Among the most important bivalve species cultivated in the north coast of Sinaloa are the oysters C. gigas (Rodríguez-Quiroz et al 2016) and C. corteziensis (Leal-Sepúlveda 2011), the clam Megapitaria squalida (Álvarez-Dagnino 2013), and the pen shell Atrina maura (Góngora-Gómez et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Forecasts for cultivation in equatorial waters of the American Pacific are that C. gigas reaches commercial size (80 mm) at 10–11 months (Lodeiros et al, ), which is a growth rate above many other reports in the subtropical Mexican Pacific (Chávez‐Villalba, ), but smaller than other cultivations performed in lagoons, where oysters of market size can be obtained in 8 months (Rodríguez‐Quiroz et al, ). However, the performance in the production of oysters in the estuary of Chone River is much higher, since it implies the shortening of the cultivation period to reach commercial size by half of the expected in the marine environment.…”
Section: Discussionmentioning
confidence: 95%
“…Revista Bio Ciencias 6, e681. Existen reportes previos en el sureste del Golfo de California (Góngora-Gómez et al, 2012;Rodríguez-Quiroz et al, 2016) indicando que el ostión Japonés alcanza su talla commercial entre 7 y 8 meses de cultivo, lo cual, coincidió con los resultados (Encomio et al, 2005), los cuales, be attributed to the continuous increase in both SH and BW (Encomio et al, 2005), which was related to the food availability. At the same time, the CI was correlated with food sources and nutrient content of oysters suggesting nutrient utilization for somatic and shell growth.…”
Section: Perkinsus Sp Incidence and Biometrics Survival And CImentioning
confidence: 96%
“…Total SL and BW of 60 specimens from each culture site were measured in situ with a vernier caliper (0.2 mm) and a portable balance (0.00 g), respectively. The growth rate of oyster was reported as body weight gain month -1 (Rodríguez-Quiroz et al, 2016). Survival was calculated by counting dead animals at each sampling and expressed as a percentage of the original number of oysters (Góngora-Gómez et al, 2012).…”
Section: Biometrics and Survivalmentioning
confidence: 99%
See 1 more Smart Citation